Writing for TV and radio a writers' and artists' companion - Teddern, Sue; Warburton, Nick (Writers' and artists' companions., 2016)
"This companion offers invaluable insights and solid, practical guidance to those keen to write for TV and radio. Part 1 explores the nature of the media. It looks at the history of writing drama and comedy for radio and TV through a consideration of its key elements and some of the most successful dramas and comedies of past and present. Part 2 includes reflections and tips from award-winning writers of film, television and radio from the UK, the US and Scandinavia. Part 3 offers practical advice on technical aspects of writing for TV and radio including character development, tructure and dialogue. It also gives guidance on how to deal with branches of the broadcasting industry, from agents and actors to producers and script editors"--Provided by publisher.